« La littérature ne fait rien toute seule » - Florent Coste (Contextes)
For many years, the question of what literature can do is a daunting one. This interview aims at reverting to its grammatical aspects. Is it possible to confer power to literature, without  giving to laughable mythology and without putting this power inside the text ? Instead of powers of literature, it seems desirable to shift the question and focus on the capacities that literature develops in its readers.